2021
DOI: 10.1186/s13020-021-00481-8
|View full text |Cite
|
Sign up to set email alerts
|

Quinic acid: a potential antibiofilm agent against clinical resistant Pseudomonas aeruginosa

Abstract: Background The biofilm state of pathogens facilitates antimicrobial resistance which makes difficult-to-treat infections. In this regard, it has been found that the compounds screened from plant extracts represent one category of the most promising antibiofilm agents. However, the antibiofilm activities and the active ingredients of plant extracts remain largely unexplored. In this background, the study is (1) to screen out the plant extracts with antibiofilm ability against Pseudomonas aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…While all the other six components have antibacterial activity and can ameliorate hyperglycemia activity. Studies have shown that quinic acid can inhibit the growth of a variety of bacteria [ 53 , 54 ], and it is a competitive inhibitor of α -amylase [ 55 ]. Chitosan/silver (CS/Ag) nanocomposite using rutin has antibacterial activity against B. subtilis [ 22 ]; in diabetic rat models, rutin can significantly reduce fasting blood sugar [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…While all the other six components have antibacterial activity and can ameliorate hyperglycemia activity. Studies have shown that quinic acid can inhibit the growth of a variety of bacteria [ 53 , 54 ], and it is a competitive inhibitor of α -amylase [ 55 ]. Chitosan/silver (CS/Ag) nanocomposite using rutin has antibacterial activity against B. subtilis [ 22 ]; in diabetic rat models, rutin can significantly reduce fasting blood sugar [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quinic acid is an organic acid mediating the ‘‘shikimate pathway’’ (shikimic acid pathway), which is a chief aromatic amino acid synthesis metabolic route exclusive to plants and microorganisms resulting in the formation of tryptophan (TRP), tyrosine (TYR), and phenylalanine (PHE) ( Averesch and Krömer, 2018 ). Quinic acid has important biological properties, including antioxidant ( Bursal et al., 2018 ), antimicrobial ( Lu et al., 2021 ; Bai et al., 2022 ) and anti HIV-1 ( Yazdi et al., 2019 ), and is a building block for the synthesis of several valuable secondary compounds, including coumaroyl and caffeoylquinic acid derivatives with significant biological activity in several drug-target areas ( Cheynier et al., 2012 ). A related compound of quinic acid, shikimic acid, was also detected in the ethanolic extract from L. spathulatum , is also key intermediate of the ‘‘shikimate pathway’’ and has a high pharmaceutical importance, such as being a precursor for the synthesis of oseltamivir (Tamiflu), the only drug against avian flu caused by the H5N1 virus ( Quiroz et al., 2014 ; Bai et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG and COG databases were used to identify the potential functions of associated metabolic pathways. The metabolism of cyanoamino acids leads to an increase in the metabolism and production of intracellular signaling molecules and proteins, as well as the creation of biofilms ( 65 ). In gastric cancer, cyanoamino acid metabolism is disturbed and disorganized, which primarily manifests as upregulation of glycine levels and the downregulation of alanine levels ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%